A Novel information retrieval mechanism with secure authentication for third party applications in cloud based integration - Neelima, G; Babu, I. Ramesh (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is a potential and assuring IT technique which helps the users to provide shared computing resources on demand. In recent days the companies are depending up on cloud resources for storage and processing of data. As the control of company’s data is handed to the third party the primary factors under utmost concern at the time of information retrieval are security and authentication. Authentication is essential in integration flows between applications for a suite of cloud services enabling users to deploy integrations with security. In my research paper we have used token based OAuth mechanism to provide authentication and query based framework for information retrieval. OAuth is a very secured authentication mechanism that is used to access the data from the source system. Secure retrieval mechanism is used for pulling the data from the cloud. The authentication technique used in our research paper is enhanced by using handshaking process with the source system and token generation in encrypted format. Analysis and implementation of this mechanism in the demo system illustrates its level of security.